2021
DOI: 10.3233/jad-201456
|View full text |Cite
|
Sign up to set email alerts
|

One-Year Aerobic Exercise Reduced Carotid Arterial Stiffness and Increased Cerebral Blood Flow in Amnestic Mild Cognitive Impairment

Abstract: Background: Central arterial stiffness and brain hypoperfusion are emerging risk factors of Alzheimer’s disease (AD). Aerobic exercise training (AET) may improve central arterial stiffness and brain perfusion. Objective: To investigate the effects of AET on central arterial stiffness and cerebral blood flow (CBF) in patients with amnestic mild cognitive impairment (MCI), a prodromal stage of AD. Methods: This is a proof-of-concept, randomized controlled trial that assigned 70 amnestic MCI patients into a 12-mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
105
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(107 citation statements)
references
References 49 publications
2
105
0
Order By: Relevance
“…Nowadays, physical activity and exercise have been widely acknowledged as effective strategies for improving AD pathology and AD-associated cognitive impairment ( Northey et al, 2018 ; Jia et al, 2019 ; de Farias et al, 2021 ). From a mechanistic perspective, macroscopically, regular exercise has been shown to alleviate some abnormalities of brain structure and function and to increase cerebral blood flow in subjects with mild cognitive impairment (MCI) and AD ( Broadhouse et al, 2020 ; Tomoto et al, 2021 ; Yu et al, 2021 ); microscopically, exercise training not only increases levels of exerkines (e.g., irisin, Lourenco et al, 2019 ; Islam et al, 2021 ) and metabolic factors (e.g., lactate, El Hayek et al, 2019 ) in the peripheral circulation, which act on the AD brain indirectly, but also exert direct neuroprotective effects by increasing levels of brain-derived neurotrophic factor (BDNF) ( Wang and Holsinger, 2018 ) and promoting adult hippocampal neurogenesis ( Choi et al, 2018 ), enhancing synaptic plasticity ( Mu et al, 2022 ), reducing neuroinflammation and oxidative stress ( Zhang et al, 2019 ), and ameliorating Aβ deposition and tau hyperphosphorylation ( Brown et al, 2019 ). Strikingly, the activity of central neurotransmitter systems seems to be strongly modulated by exercise.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, physical activity and exercise have been widely acknowledged as effective strategies for improving AD pathology and AD-associated cognitive impairment ( Northey et al, 2018 ; Jia et al, 2019 ; de Farias et al, 2021 ). From a mechanistic perspective, macroscopically, regular exercise has been shown to alleviate some abnormalities of brain structure and function and to increase cerebral blood flow in subjects with mild cognitive impairment (MCI) and AD ( Broadhouse et al, 2020 ; Tomoto et al, 2021 ; Yu et al, 2021 ); microscopically, exercise training not only increases levels of exerkines (e.g., irisin, Lourenco et al, 2019 ; Islam et al, 2021 ) and metabolic factors (e.g., lactate, El Hayek et al, 2019 ) in the peripheral circulation, which act on the AD brain indirectly, but also exert direct neuroprotective effects by increasing levels of brain-derived neurotrophic factor (BDNF) ( Wang and Holsinger, 2018 ) and promoting adult hippocampal neurogenesis ( Choi et al, 2018 ), enhancing synaptic plasticity ( Mu et al, 2022 ), reducing neuroinflammation and oxidative stress ( Zhang et al, 2019 ), and ameliorating Aβ deposition and tau hyperphosphorylation ( Brown et al, 2019 ). Strikingly, the activity of central neurotransmitter systems seems to be strongly modulated by exercise.…”
Section: Introductionmentioning
confidence: 99%
“…Observational studies have found that sedentary older adults had lower cerebral blood flow than active older adults ( Rogers et al, 1990 ; Thomas et al, 2013 ; Knight et al, 2021 ; Li et al, 2021 ). Recently, a small randomized controlled trial involving a 1-year aerobic exercise intervention reported increased cerebral blood flow in the exercise group ( Tomoto et al, 2021 ).…”
Section: Physiological Mechanismsmentioning
confidence: 99%
“…The vascular mechanisms for the observed increase in hypocapnic CVMR (vasoconstriction) and decrease in hypercapnic CVMR (vasodilation) with AET can only be speculated. Moderate-to-vigorous intensity AET may reduce the central and large cerebral artery stiffness, improve cerebral endothelial function (e.g., endothelium-dependent dilation), and decrease cerebral blood vessel wall smooth muscle tone (e.g., arterial stiffness) (38,44). For example, habitual exercise improved endothelium-dependent vasodilation measured from peripheral arteries, and decreased large elastic artery stiffness in healthy middle-aged and older adults including patients with MCI (38,44).…”
Section: Effects Of Aet On Cvmrmentioning
confidence: 99%
“…Moderate-to-vigorous intensity AET may reduce the central and large cerebral artery stiffness, improve cerebral endothelial function (e.g., endothelium-dependent dilation), and decrease cerebral blood vessel wall smooth muscle tone (e.g., arterial stiffness) (38,44). For example, habitual exercise improved endothelium-dependent vasodilation measured from peripheral arteries, and decreased large elastic artery stiffness in healthy middle-aged and older adults including patients with MCI (38,44). If AET reduces cerebral arterial stiffness, improves cerebral endothelial function, and reduces the cerebrovascular tone, cerebral vasoconstriction reserve during hypocapnia may increase whereas cerebral vasodilation reserve (i.e., the maximal vasodilation from baseline before CO 2 stimuli) during hypercapnia may decrease due to baseline vasodilation before CO 2 stimuli, consistent with the observations that AET improved endothelial function at rest (44).…”
Section: Effects Of Aet On Cvmrmentioning
confidence: 99%